ESTETIKA DESAIN POSTER ALEKSANDR RODCHENKO BERDASARKAN KACAMATA TEORI EKSPRESI CROCE-COLLINGWOOD DAN FORMALISME BELL-FRY - Alfiansyah Zulkarnain; Jennifer Claudy (Universitas Mercu Buana, 2021)
A lot of contemporary analysis on Aleksandr Rodchenko’s design works is done through the critical lens of avant-garde and humanities. With the rise of effort to bring back relevance of traditional aesthetics as the point of view to look at art and design, there is a space to reread Rodchenko’s work. This paper will analyze the aesthetic of Rodchenko’s poster design titled “Books: The Advertisement Poster for the Lengiz Publishing House”. The analysis will be conducted through two different perspective: through the lens of Croce and Collingwood’s Expression Theory (or CC Theory), and the lens of Bell & Fry’s Formalism. The aim of this study is to determine whether aesthetical judgement could be given on constructivism poster design through both lens. The method of analysis is using qualitative research method based on literature study. The poster then will be investigated through each criteria of essence of art from each point of view. In the end, it could be concluded that the poster has significant aesthetic value from each point of view.